การศึกษาผลกระทบเนื่องจากรูปแบบของครีบต่อการถ่ายเทความร้อน โดยใช้เทคนิค CFD - ณรงค์ ทิพย์มงคลศิลป์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study effects of fin configuration to the flow pattern and temperature distribution of air including heat transfer performance and fluid mechanism occurred using mathematical model. The simulation were solving a set of conservation equations, consisting of continuity equations, momentum equations, energy equations and turbulent models. Computational Fluid Dynamics (CFD) technique, i.e. PHENICS program, was used in this study. The reliability and suitability of model and program is validated against detailed experiment data of R.S. Mullisen, et al. for validating the accuracy of mathematical model before utilize this model in this study. The thesis was studied on the effects of fin configuration to the heat transfer performance and fluid behavior by simulating three categories of fin configuration, consisting of Inline Continuous Plate Fin, Inline Plate Fin and Louver Plate Fin. The result of the simulation shows that the heat transfer performance in case Inline Continuous Plate Fin is less than in case Inline Plate Fin and Louver Plate Fin, respectively. However, the Inline Continuous Plate Fin has given the lowest value in term of the pressure drop. In addition to the simulation result, the reason of fin configuration affecting to the heat transfer performance is due to the 2-differential characteristic of the air flowing through these 3 categories of the fin configuration, the thermal boundary layer and the vortex shedding. The air flowing in the thermal boundary layer area has low velocity and the dominant heat transfer characteristic of this area is the conduction phenomena. In case of the vortex shedding area, air has higher velocity and has more turbulence while the vortex shedding characteristic also causes the better heat transfer performance in this area. Furthermore, the dominant heat transfer phoenomena of this area is the convection phoenomera.